Lekor Den Enterprise: Keropok Lekor / Norfazarifah Ahmad Fazli... [et al.] - Ahmad Fazli, Norfazarifah; Rosdi, Nur Fatin Nabilla; Mohamadon, Siti Sara; Sabarudin, Solehah; Nokman, Zamzuliana (2013)
As for the business, we are providing a special, delicious taste, trusted and Halal Keropok Lekor around the Asians and especially for the Malaysians. As we go through with the changes of environment, people nowadays take simple food on their own daily meals.